Views of survivors of stroke on benefits of physiotherapy. Issue 2 (June 1994) - Pound, P; Bury, M; Gompertz, P; Ebrahim, S
Abstract : OBJECTIVE--To describe the components of physiotherapy valued by survivors of a stroke. DESIGN--Qualitative study using in-depth interviews. SETTING--Two adjacent districts in North East Thames Regional Health Authority. PATIENTS--82 survivors of stroke taken consecutively from a stroke register when they reached the tenth month after their stroke, 40 of whom agreed to be interviewed. MAIN MEASURES--Content analysis of interviews. RESULTS--Patients who agreed to the interview were significantly less likely to be disabled 12 months after stroke than those who did not. Twenty four patients had received physiotherapy, and these were more disabled than those who had not. Patients appreciated physiotherapy. It was believed to bring about functional improvement; the exercise component was valued because it was perceived to keep them active and busy and exercise programmes to follow at home were also valued for the structure they gave to each day; and therapists were considered a source of advice and information and a source of faith and hope. CONCLUSIONS--Many of the positive aspects of caring which patients described in the context of physiotherapy could be incorporated into the mainstream of rehabilitation care and training. However, health professionals need to be careful not to promote false expectations about recovery. IMPLICATIONS--The outcome of treatment is of critical importance to patients and should become a central dimension of patient satisfaction questionnaires. The impact of physiotherapy is not confined to reducing physical disability but may also affect wellbeing. The choice of outcome measures in rehabilitation research should reflect this situation.